(untitled) (Gaceta de Ciencias Veterinarias, 2018)
Foot-and-mouth disease (FMD), one of the most transmissible viral diseases of animals, is of great economic importance due to its impact on the production and international trade of animals and their products. In Venezuela, the disease still persists with endemic circulation throughout its territory. As it is indistinguishable from other vesicular diseases and other diseases confusable with FMD, its definitive diagnosis is made by laboratory, which in turn is very important for eradication campaigns to initiate the application of control measures that will prevent further spread of the disease. In Venezuela, in the framework of the attention of the suspected outbreak to FMD (cases sampled), is presented the situation in which the causal agent of the suspected disease is not determined (unconfirmed cases), being reported as negative to FMD and other diseases vesicular and / or confusable with FMD. Among the causes of absence of confirmation by laboratory is the remission of unsatisfactory samples. As a contribution to the national eradication program, the work includes a review of manuals for collection and referral of samples and addresses some aspects related to sampling for the diagnosis of FMD in Venezuela, of importance in the improvement of performance in the sampling and, consequently, in the diagnosis, attention and control of the outbreaks, and more accurate estimation of the incidence of the disease in the country.